Models for a Better Management of Linear Parks - Gusteler F.; López R.; Faggi A. (European Scientific Journal, ESJ, 2017)
This project provides a strategy to improve the quality of linear parks. It is based on recognizing the type of linear park in question through the activities carried out by users and the structural and functional characteristics of the green area. With this information we can establish or check the existence of essential elements to guarantee benefits to users. Three conceptual models were defined from four linear parks in the metropolis of Buenos Aires and the city of Formosa according to the supply and demand of the services they offer. For which it was necessary to consider the infrastructures and vegetation they present, uses and benefits of the linear parks and the activities that are carried out.